English Language Activities In Computer-Based Learning Environment: A Case Study In ESL Malaysian Classroom - Nadzrah Abu Bakar, (Penerbitan UKM, 2007)
Computer based learning environment has been widely discussed, especially in finding a better way to incorporate computer-based activities in the classroom. Lately, the use of computers in the classroom is particularly important in the context of teaching and learning English as a second language. This paper aims to investigate and to understand how computer-based activities are organized in a school situation that is totally dependent on the syllabus. This study is a case study that incorporates classroom observations, field-notes, interviews and written documents. Both computer-based activities and non computer-based activities in ESL classrooms were recorded and anaylsed. This study concludes that the opportunities for students to learn English as a second language using computers are very wide, and the use of L2 can be increased if authentic computer-based activities can be incorporated in the lesson